The microstructure of nuclear graphite binders - Wen, K; Marrow, T; Marsden, B (2008)
The microstructures of the binder in two grades of nuclear graphite, Gilsocarbon graphite and Pile Grade A graphite, were characterized by light microscopy, transmission electron microscopy and high resolution transmission electron microscopy. A variety of structures of carbon were observed, including a well-graphitized structure, nanosized graphite particles, quinoline insoluble (QI) particles, chaotic structures and non-graphitizing carbon. QI particles were observed on the surface of mesophase spheres as well as inside mesophase spheres. The aggregation of QI particles on the surface of mesophase spheres, or very near the surface in mesophase spheres, appears to have a significant influence on the development of the mesophase structure, resulting in refinement of the mesophase spheres before their coalescence. The chaotic structure, which is turbostratic and isotropic, is suggested to have developed from the isotropic pitch remaining between mesophase spheres. The non-graphitizing carbon consisted of flat and curved single layer graphene fragments with a size typically less than 1 nm. The formation of the various structures in the two graphites is attributed to the introduction of different pitches at stages of the graphite manufacture. © 2007 Elsevier Ltd. All rights reserved.